Human pathogenic bacteria in sea fish - siakap (SEA PERCH, lates calcarifer) and ikan merah (RED SNAPPER, Lutjanus sanguineus - Khan Chowdhury, Ahmed Jalal; Nordin, Noor Faizul Hadry; Masseren, Noor Isma Yanti; Yunus, Kamaruzzaman; Saad, Shahbudin (2010)
The presence of fish spoilage and human pathogenic bacteria in ice-chilled and spoiled Siakap (Sea perch Lates calcarifer) and ikan merah (Red snapper, Lutjanus sanguineus) were studied. Microbiological analysis was performed and the isolated bacteria were identified up to the species level by using API 20 E identification system. The study portrays that Vibrio fluvialis, Proteus mirabilis, Proteus vulgaris, Brucella sp. and Ochrabactrum anthropi were the human pathogenic bacteria found in sea perch while Vibrio fluvialis, Proteus mirabilis and Proteus vulgaris were detected in red snapper. In this study, Vivrio fluvialis was the fish spoilage bacteria found in both fishes while Shewanella putrefaciens was detected specifically in sea perch and Photobacterium damsala was detected in red snapper. In fact poor hygienic of fish handling practices and improper fish storage conditions have been observed to be the potential contamination sources of these bacteria. The present findings might be instrumental to aid both the food safety regulatory bodies and the Hazard Analysis Critical Control Point System in setting up new standards and guidelines for the awareness on post harvest fish handling practices in the public fish market and sea food restaurants.